2022
DOI: 10.53730/ijhs.v6ns1.6230
|View full text |Cite
|
Sign up to set email alerts
|

effect of moringa leaf extract in increasing Hb levels of pregnant women during COVID-19 pandemic in Parigi Regency, Central Sulawesi, Indonesia

Abstract: Background; The Covid-19 pandemic has a major impact on socioeconomic conditions and public health, especially pregnant women. The availability of food and nutrition will be greatly reduced due to limited mobility which will have an impact on the incidence of anemia in pregnant women. Thus, it is important to use moringa leaf extract as a local resource. Aim To find out the effect of Moringa leaf extract in reducing the incidence of anemia (hemoglobin levels) in pregnant women during the Covid-19 pandemic in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
1
0
1
Order By: Relevance
“…The hemoglobin level was 0.90g/dl higher among fresh moringa leaf consumers than non-consumers. This is in line with previous studies conducted in Indonesia, India, Senegal, Bangladesh and recent reviews 37 , 38 , 42 , 51–56 where the intake of moringa in different forms treats anemia. This may be due to the nutrient content of moringa.…”
Section: Discussionsupporting
confidence: 93%
“…The hemoglobin level was 0.90g/dl higher among fresh moringa leaf consumers than non-consumers. This is in line with previous studies conducted in Indonesia, India, Senegal, Bangladesh and recent reviews 37 , 38 , 42 , 51–56 where the intake of moringa in different forms treats anemia. This may be due to the nutrient content of moringa.…”
Section: Discussionsupporting
confidence: 93%
“…In our investigation, the mean placental thickness rose with gestational age, from 1.61±0.26 cm at 11-20 weeks to 3.35±0.26 cm at 31-40 weeks, which nearly mirrored the findings of Dudley et al, who found that placental thickness grew from 15 mm at 11 weeks to 37.5 mm at 39 weeks [17]. The placental thickness increased gradually from a mean value of 20 mm at 16 weeks of gestation to 30 mm at 28 weeks in a research of a similar nature done by Jauniaux et al [18].…”
Section: Discussionsupporting
confidence: 80%
“…Because subnormal placental thickness for a gestational age may be the early sign of foetal growth retardation, this link between placental thickness and growth metrics is useful. Jauniaux et al and Dombrowski et al established a correlation between an increase in placental thickness and hypertensive problems of pregnancy and/ or subsequent sluggish foetal growth, around mid-gestation [18,21]. According to Ko et al, a second trimester increase in placental thickness is a highly sensitive indicator of the development of foetal hydrops associated with alpha-thalassemia in high-risk groups [22].…”
Section: Discussionmentioning
confidence: 99%
“…Salah satu intervensi yang menjanjikan adalah penggunaan daun kelor (Moringa oleifera). Daun kelor yang diberikan pada penelitian yang direview dapat berupa daun kelor segar (Derbo & Debelew, 2023), seduhan (Tampubolon et al, 202, Susanti et al, 2021), sup daun kelor (Atika et al, 2021, Thenmozhi P et al, 2020, maupun ekstrak daun kelor dalam bentuk kapsul (Novarta et al, 2023, Nur et al, 2022, Hartati & Sunarsih, 2021…”
Section: Introductionunclassified